Glucagon-Like Peptide-2 Modulates Enteric Paneth Cells Immune Response and Alleviates Gut Inflammation During Intravenous Fluid Infusion in Mice With a Central Catheter - Deng, Guifang; Lei, Qiucheng; Gao, Xuejin; Zhang, Yupeng; Zheng, Huazhen; Bi, Jingcheng; Wang, Xinying (Frontiers in Nutrition, 2021)
Background: Glucagon-like peptide-2 (GLP-2) has protective effects on gastrointestinal functions. Our previous study found that GLP-2 could significantly reduce intestinal permeability and bacterial translocation in total parenteral nutrition (TPN) animal model. However, the effects of GLP-2 on the impairment of the intestinal Paneth cells immune function and gut inflammation during intravenous fluid infusion mainly consisted of nutritional materials is currently scattered. Objective: The current study was aimed to investigate the efficacy of the GLP-2 in alleviating gut inflammation and modulating enteric Paneth cells immune response in parenterally fed mice and its underlying mechanisms. Methods: Thirty-six male ICR mice underwent venous catheterization were divided into 3 groups: Chow, TPN, and TPN+GLP-2 groups. GLP-2 was administered intravenously at 60μg/day for 5 days. The small intestine tissue and serum samples were collected on the 7th day. Results: Compared with the TPN group, the expression of tight junction proteins occludin and claudin-1 were significantly increased in the TPN+GLP-2 group. In addition, the expression of lysozyme, sPLA2, insulin-like growth factor-1, and epithelial protection and repair genes were improved in the TPN+GLP-2 group. The levels of IL-6 and TNF-α proteins and mRNAs in the ileum tissues were remarkably reduced in the TPN+GLP-2 group, while IL-10 protein and mRNA level were elevated in the TPN+GLP-2 group (all p＜0.05). Moreover, the TPN+GLP-2 group has higher levels of serum endotoxin, D-lactic acid, and MPO than those of the TPN group. Conclusions: GLP-2 alleviated gut inflammation and improved enteric Paneth cells immune responses through intravenous fluid infusion, possibly by improving the functioning of epithelial protection and repair, and reducing mucosal inflammatory responses.